A thromboxane A2/prostaglandin H2 receptor antagonist (S18886) shows high antithrombotic efficacy in an experimental model of stent-induced thrombosis - Vilahur, Gemma; Casaní, Laura; Badimon, Lina (Thrombosis and Haemostasis, 2007)
Acute thrombosis is a threat in patients undergoing percutaneous coronary intervention with stent implantation. Our objective was to determine if stent-induced thrombus formation could be inhibited by oral treatment with a thromboxane A2/prostaglandin H2 receptor antagonist (TPr; S18886) as an alternative to standard therapy. Pigs were allocated in the following treatment (p.o) groups: I) clopidogrel (CLOP); II) ASA; III) S18886; IV) ASA+CLOP; and V) placebo-control. Damaged vessel was placed in the Badimon chamber containing a stent and perfused at 212/s.Antithrombotic effects were assessed as 111In-platelet deposition (PD) in two series (60 and 180 min after drug intake). Fibrin(ogen) deposition, light transmittance aggregometry (LTA; collagen, U46619, and ADP), and bleeding time (BT) were also evaluated. After 60 min S18886 reduced PD ≤48%, 40%, and 35% vs placebo, CLOP-, and ASA-treated ani mals, respectively (P<0.05), while ASA+CLOP showed a 58% reduction versus placebo (P<0.01).After 3 hours, ASA+CLOP decreased PD by 55%, S18886 by 40%, CLOP alone by 28% (P>0.05), and ASA showed no inhibition versus placebo. Similar effects were found in S18886– and ASA+CLOP-treated animals at both times. Fibrin(ogen) deposition followed the same pattern. Collagen-induced LTA was significantly reduced by ASA, ASA+CLOP, and S18886; S18886 abolished U46619-induced LTA; and, CLOP±ASA reduced ADP-induced LTA in a time-dependent manner. TPr blockade did not prolong BT, whereas CLOP±ASA significantly did (P<0.0001). In conclusion, blockade of theTPr provided a fast and potent platelet inhibitory effect in a porcine model of in-stent thrombosis comparable to that of blocking both the ADP receptor and cyclooxygenase activation; in addition,TPr provided a more favorable bleeding risk profile.
Keywords: Thrombosis; thromboxane; aspirin plus clopidogrel; stents